2014
DOI: 10.1177/0300985814556185
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Papillomas of the Conjunctiva in Dogs

Abstract: Papillomas of the conjunctival surface in people can be of viral or nonviral origin and are found in high association with human papillomavirus. Canine conjunctival papillomas are seldom described, and published accounts have mostly been associated with canine oral papillomavirus infection. Here, we describe conjunctival squamous papillomas that do not express papillomavirus proteins and compare them with papillomavirus-associated conjunctival papillomas. Conjunctival squamous papillomas presented a distinct h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
1
5
0
3
Order By: Relevance
“…Papillomavirus has been detected in conjunctival plaques and viral papillomas, and an eyelid squamous cell carcinoma in dogs [23, 28, 39]. However, Beckwith-Cohen et al showed that papillomavirus was not present in 10 conjunctival squamous papillomas or normal conjunctival tissue from one dog [39]. Our current study is consistent with the Beckwith-Cohen study as papillomavirus was not present in normal conjunctival tissue or tissue from canine lobular orbital adenomas.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Papillomavirus has been detected in conjunctival plaques and viral papillomas, and an eyelid squamous cell carcinoma in dogs [23, 28, 39]. However, Beckwith-Cohen et al showed that papillomavirus was not present in 10 conjunctival squamous papillomas or normal conjunctival tissue from one dog [39]. Our current study is consistent with the Beckwith-Cohen study as papillomavirus was not present in normal conjunctival tissue or tissue from canine lobular orbital adenomas.…”
Section: Discussionsupporting
confidence: 89%
“…Several other studies have evaluated normal and abnormal canine ocular tissue for the presence of papillomavirus. Papillomavirus has been detected in conjunctival plaques and viral papillomas, and an eyelid squamous cell carcinoma in dogs [23, 28, 39]. However, Beckwith-Cohen et al showed that papillomavirus was not present in 10 conjunctival squamous papillomas or normal conjunctival tissue from one dog [39].…”
Section: Discussionmentioning
confidence: 99%
“…ab2417, Abcam, Cambridge, UK) were 100-fold diluted in PBST and applied to the slides for incubation for one hour at room temperature. This antibody broadly reacts to several types of CPV, BPV, HPV, and Zalophus papillomavirus [38][39][40][41][42]. The endogenous peroxidase activity was blocked by incubating the slides with 3% H2O2 in methanol for 10 min.…”
Section: Immunohistochemistry Staining Of Viral Antigensmentioning
confidence: 99%
“…Moreover, recent publications suggested that, squamous papilloma of skin and conjunctiva in dogs are not connected with papillomaviruses. 7 …”
Section: Introductionmentioning
confidence: 99%